ANALISIS KEKUATAN MATERIAL KOMPOSIT KOMPOSISI HGM & EPOXY DENGAN PENGUAT SERAT ALAM SEBAGAI BAHAN ALTERNATIF PELINDUNG TOE CAP SEPATU SAFETY - Rendyatama Aprila; Boy Rollastin; Husman Husman (Prosiding Seminar Nasional Inovasi Teknologi Terapan, 2022)
Composite is the process of mixing or combining two or more materials where the two materials have different properties, the results of the mixture can be referred to as (composite materials). The purpose of this research was to make composite specimens made from epoxy resin, Hgm, balsa wood fiber as natural reinforcement and carried out impact and tensile tests to determine whether the strength of the composite could be an alternative as a substitute for protective Toe caps for safety shoes. The balsa wood used in the tensile test specimen is in the form of sticks with a length of 16cm and a thickness of 3mm which has 3 test parameters, namely 1 balsa stick, 2 balsa sticks, and 3 balsa sticks. As for the impact test, 1 stick of balsa stick with a length of 7.5 cm and a thickness of 3 mm. Keywords: Composite, Balsa wood, Hgm, Epoxy, Impact and Tensile